Ocular biometric parameters in South-Indian children with myopia – A hospital-based retrospective descriptive analysis - Sandra Ganesh; Rebecca Claire Lusobya; Mohammed Sithiq Uduman; Reshma Rajan; Nisha Rajendran; Kripa Sanjeev; Kalpana Narendran (Indian Journal of Ophthalmology, 2025)
Aim: This study aims to profile the ocular biometric parameters in a large group of children of South-Indian ethnicity who visited our outpatient children’s department and were diagnosed with myopia. Methods: Children <15 years old diagnosed with myopia (Jan 2022–Oct 2023) and who had ocular biometry readings recorded were included. Their demographics, axial length (AL), anterior chamber depth (ACD), spherical equivalent (SE), corneal radius of curvature (CR), and AL/CR ratio were analyzed. Results: The study included 3728 myopic children; the mean age was 11.85 (4–15) years, and 52.8% were girls. Mean SE was −3.98 D. The mean (SD) AL, ACD, CR, and AL/CR ratio were 24.64 (1.32), 3.73 (0.40), 7.61 (0.27), and 3.24 (0.16), respectively. Female gender was associated with shorter AL, ACD, CR, and AL/CR ratios (P < 0.001) across all age groups. There was a significant increase in ACD with age in both sexes (P < 0.001). A 1-unit (mm) increase in AL was associated with an SE increase of −1.65 D (CL: −1.70 to −1.60). AL/CR ratio could explain 71% of the total variance in SE (P < 0.001). SE showed a mild correlation with age (rho = 0.14, P < 0.001) and ACD (rho = −0.03, P = 0.041) and a stronger correlation with AL (rho = −0.68, P < 0.001) and AL/CR (rho = −0.83, P < 0.001). Conclusion: In this hospital-based study, AL and AL/CR ratios strongly correlate with SE, and the AL/CR better explains the total variance in SE than AL alone in children with myopia.